(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
Gustav Klimt and Peter Altenberg are two figures within Viennese fin-de-siècle cultural production whose art may reveal a perception of local Jewish culture through their different foci on the non-European female body image. Both men have moments in their career, when their attention turns to non-European cultures, through which they inadvertently represent and interpret their own. A selection of these two artists’ most well-known works demonstrate two frameworks in which Viennese Jewishness can be read through an alignment of the female body with Asian and African cultures.